Influence of Different Drying Methods on Proximate and Mineral Composition of Pea Pods - , Anjali Kumari; , Monika Sood; , Julie D. Bandral; , Neeraj Gupta; , Ankita Choudhary (Archives of Current Research International, 2025)
Pea pods, by-products of the pea processing industry, are a rich source of nutrients but are frequently disposed of incorrectly. In this study, pea pod powder (PPP) was developed by using different drying methods such as viz., sun, solar, tray, microwave, freeze and osmotic drying and was analyzed for its proximate and mineral composition. The results revealed that dried pea pod powder contained moisture, and the ash content of dried pea pods ranged from 8.95 to 5.10% and 7.74 to 5.87%, respectively. The highest crude protein, crude fat and crude fibre content of 15.02, 1.90 and 8.95 %, respectively, were recorded in freeze-dried (FD) pea pod powder. Further, FD PPP recorded the highest potassium, iron and magnesium content of 1832.37, 856.47 and 10.45 mg/100g, respectively, while the least potassium, iron and magnesium content of 1010.29, 718.56 and 5.84 mg/100g, respectively, were observed in the sun drying (SD) pea pod powder. According to the study, FD pea pod powder retained more of its proximate components, whereas sun-drying (SD) caused a larger loss of nutrients. When creating functional foods that offer health benefits, the best-dried pea pod powder can be utilized.